Oblique lateral internal fusion combined with percutaneous pedicle screw fixation in severe lumbar spinal stenosis: clinical and radiographic outcome - Chen Liu; Yin Geng; Yifeng Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Oblique lumbar interbody fusion (OLIF) has been a popular technique for treating lumbar degenerative diseases. Previous studies have shown its efficiency in lumbar spinal stenosis; yet, only a few studies have investigated its application to severe lumbar spinal stenosis. Herein, we investigated the clinical and radiographic outcome of OLIF with percutaneous pedicle screws in the treatment of severe lumbar spinal stenosis. Methods A total of 15 patients who underwent OLIF with percutaneous pedicle screws were retrospectively analysed. All patients were diagnosed with severe lumbar stenosis (Schizas grade C or D) through preoperative magnetic resonance image (MRI) and received OLIF combined with percutaneous pedicle screw surgery. Clinical outcomes, including visual analogue scale (VAS)-back and VAS-leg scores, and Oswestry Disability Index (ODI), as well as mean disc height (DH), mean foraminal height (FH), segmental lumbar lordosis (SLL) and cross-sectional area (CSA) of the spinal canal, were analysed before and after surgery and at the last follow-up. Intraoperative data, complications and fusion rate were also investigated. Results OLIF combined with percutaneous pedicle screws was performed on 18 segments in 15 patients. Mean follow-up was 23.1 ± 4.6 months (range 15–29 months). VAS-back, VAS-leg, and ODI scores were significantly improved at the last follow-up. DH increased from 8.86 ± 3.06 mm before surgery to 13.31 ± 2.14 mm after; at the last follow-up, DH was 11.69 ± 1.87 mm. FH increased from 17.85 ± 2.26 mm before surgery to 22.09 ± 1.36 mm after; at the last follow-up, FH was 20.41 ± 0.99 mm. CSA of the spinal canal increased from 30.83 ± 21.15 mm2 before surgery to 74.99 ± 33.65 mm2 after the operation and 81.22 ± 35.53 mm2 at the last follow-up. The segmental LL before surgery, after surgery and at last follow-up was 20.27 ± 6.25 degrees, 20.83 ± 6.52 degrees and 19.75 ± 5.87 degrees, respectively. All patients have gained fusion at the last follow-up. Conclusion OLIF with percutaneous pedicle screws could achieve satisfactory clinical and radiographic effects through indirect compression by increasing DH, FH and CSA of the spinal canal in severe lumbar stenosis patients.